Performance of Dynamometer with Sensor Type Single Bar for Measuring Drive Power of Rotary Friction Welding Machine - Yohanes Yohanes; Novri Andri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
This study aims to determine the performance of the dynamometer design as a measure of mechanical power on a rotary friction welding machine. The design of the dynamometer includes the design, manufacture, calibration, and testing of the dynamometer. The design and manufacture of strain dynamometers is adjusted to the motor of the rotary friction welding machine at the University of Riau's Mechanical Engineering Production Technology Laboratory. The design of the strain dynamometer has a dimension of 175 mm × 3 mm × 50 mm and serves to determine the motor torque value with the help of a 120 ohm strain gauge sensor. The device designed is equipped with an electrical microcontroller device and an optocoupler sensor to measure the angular speed of the motor. Next, the dynamometer performance testing is performed on the rotary friction welding machine. The results of testing in the rotary welding process, the greater the pneumatic pressure exerted during welding, the greater the measured power. The largest measured power value is 2452.92 Watt in the forging process, and the smallest measured power value is 2050.24 Watt in the first time of the initial motor rotation. After doing the research, it can be concluded that the tools designed and built can work and have a fairly good performance.